Métodos adaptativos e formulações analíticas simplificadas para avaliação de abalroamento de navios - Ramos Alvarez, Nain Maximo (2019)
In numerical analysis of crashworthiness ship structures scenarios it is common to use dense uniform refinement in the collision zone, requiring a high computational time. To reduce this expense, a methodology called the non-local adaptive mesh refinement method (MMA-N) was developed, which uses refinement indicators in the mesh elements to establish the adaptive process. These indicators are based on non-local variables such as stress triaxiality or damage parameter. Simplified analytical methodologies are widely used alternatives, which allow quick solution but are less accurate. The existing works on this subject consider axisymmetric strains, produced by indentors with simple geometric shapes. In this thesis an analytical methodology was developed in which a bulb with a shape close to a ship is considered, producing in the collided panel a more realistic strain state. To verify the numerical and analytical methodologies developed, experimental tests were performed that simulate two scenarios of collision of ships. For the numerical simulations it is necessary to know the material fracture strain versus stress triaxiality curve, and for this purpose a material testing program was performed with specimens with specific geometries to produce different stress triaxialities during fracture. The numerical and analytical results applying the developed methodologies were in good agreement with experimental tests produced in this thesis and data published in the literature.